An intracategorical intersectional framework for understanding 'supportability' in womxn's narratives of their pregnancy - Kalyanaraman, Yamini (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
In South Africa, the current Maternal Mortality Ratio (MMR) is 135 per 100,000 live births, with a long way to go before it can achieve the Sustainable Development Goal (SDG) global target of under 70 per 100,000 live births by 2030. This research project focuses on the narratives of pregnant womxn in the Eastern Cape Province, using an intracategorical intersectional framework and Macleod's 'supportability' model as a base. The study aims to locate womxn's pregnancies within the interweaving biological, psychological, social, economic, cultural and political contexts within which they occur, while focusing specifically on the aspect of 'supportability'. Through purposive sampling and snowballing methods, the research team recruited participants who were 18 years and older, in or past the second trimester of their pregnancy, and able to access antenatal care. Research data were produced using photo-elicitation techniques on 92 photographs and narratives from 32 interviews. An intersectional thematic analysis was used to generate themes, which highlighted different aspects that enabled or hindered pregnancy 'supportability'. In accordance with prior research, it was revealed that womxn found emotional and tangible support the most beneficial. Findings from this study reveal the interconnectedness between a womxn's personal (emotional, physical and cognitive) experiences of pregnancy, the micro-interactions of support (un)available from partners, family, friends, healthcare workers, workplaces and community members, and the macrostructures of socioeconomic policies, religiosity, cultural practices and healthcare systems. For example, gendered perceptions (a macro-structure) influence the instrumental support provided by partners (a micro-interaction), which impacts the womxn's well-being (personal). Certain themes that emerged from the different narratives were: the importance of making available pregnancy-related information to the womxn; a desire for non-judgement and acceptance of their pregnancies within their community; and the need for adequate communication in microinteractions. The findings of this research also indicate that, despite the financial tensions inherent in each womxn's life, the participants were driven by overarching hopes for their child's future.
Keywords: Pregnancy -- Psychological aspects -- South Africa; Prenatal care -- South Africa; Pregnant women -- South Africa -- Psycology; Medical care -- South Africa -- Eastern Cape